A study on the customers' demand for education loan (Approved colleges/Universities education scheme [ACES]) offered by Bank Utama (Malaysia) Berhad in Sarawak since its introduction in year 2000 until end of Year 2002 / Florence Sundang - Sundang, Florence (2003)
Education is a booming industry and has been one of the leading industries in some major countries. Malaysia has only recently started out to capture this market and is aiming to be the leading educational provider in South-East Asia. In August 2000, Bank Utama (Malaysia) Berhad has approved a product called Approved College/University Education Scheme (ACES) – a type of loan scheme formulated by the Bank to provide financing to deserving students who want to further their education locally. In June 2001, the package was subsequently extended to undergraduate students who were enrolled in both local and foreign universities or colleges or those courses which need to be completed overseas and must be approved by the Ministry of Education.